Cooperation Practices: Survival Strategies, Alternative Movements or Capitalism Re-embedment? (Prácticas cooperativas: ¿estrategias de supervivencia, movimientos alternativos o reincrustación capitalista?) - Raquel Alquézar Crusellas; Patricia Homs Ramírez de la Piscina; Núria Morelló Calafell; Diana Sarkis Fernández (Ars & Humanitas, 2014)
Cooperation practices are the backbone of human society's social and material reproduction. The neoclassical discourse has attempted to hide the importance of cooperation in social and material reproduction. Nevertheless, human history offers plenty of examples where reciprocity, cooperation and/or solidarity are the core of economic practices.